THE ANALYSES OF HUMAN RESOURCES MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION (A case Study at Madrasah Aliyah Al-Manshury Sungai Bakau Besar Laut) - Sumiyati (IJGIE (International Journal of Graduate of Islamic Education), 2020)
Scope: In general, human resource management is a process of carrying out the continuity of duties of organizational members as resources that can support all tasks and functions for the achievement of organizational or institutional goals. In the context of education as a formal educational institution, schools or madrassas strongly emphasize the improvement in the quality of the human. Objective: This study aimed to determine the effort to empower human resource management in improving the quality of Madrasah Aliyah Al Manshury Sungai Bakau Besar Laut. Method: This study used a qualitative approach. The data analysis technique used is an interactive model analysis with stages: data collection, data reduction, presentation of data and conclusions or verification. Findings: This institution has successfully functioning its human resources effectively; staring from well develoed its school profile, school vision and mission, well infrastructure arragement, quality management activities including staff welfare, staff training, assesment of work perforamnace, recruitment, library and practicum laboratory, employers welfare, good staff selection management and quality control. Conclusion: The madrasah has be able to improve the quality of education that has been determined in the vision and mission in achieving its main goal. However, it needs further research for improvement.